Science-based health innovation in Ghana: health entrepreneurs point the way to a new development path - Singer Peter A; Daar Abdallah S; Al-Bader Sara (BMC, 2010)
Abstract Background Science, technology and innovation have long played a role in Ghana's vision for development, including in improving its health outcomes. However, so far little research has been conducted on Ghana's capacity for health innovation to address local diseases. This research aims to fill that gap, mapping out the key actors involved, highlighting examples of indigenous innovation, setting out the challenges ahead and outlining recommendations for strengthening Ghana's health innovation system. Methods Case study research methodology was used. Data were collected through reviews of academic literature and policy documents and through open-ended, face-to-face interviews with 48 people from across the science-based health innovation system. Data was collected over three visits to Ghana from February 2007 to August 2008, and stakeholders engaged subsequently. Results Ghana has strengths which could underpin science-based health innovation in the future, including health and biosciences research institutions with strong foreign linkages and donor support; a relatively strong regulatory system which is building capacity in other West African countries; the beginnings of new funding forms such as venture capital; and the return of professionals from the diaspora, bringing expertise and contacts. Some health products and services are already being developed in Ghana by individual entrepreneurs, which are innovative in the sense of being new to the country and, in some cases, the continent. They include essential medicines, raw pharmaceutical materials, new formulations for pediatric use and plant medicines at various stages of development. Conclusions While Ghana has many institutions concerned with health research and its commercialization, their ability to work together to address clear health goals is low. If Ghana is to capitalize on its assets, including political and macroeconomic stability which underpin investment in health enterprises, it needs to improve the health innovation environment through increasing support for its small firms; coordinating policies; and beginning a dialogue with donors on how health research can create locally-owned knowledge and be more demand-driven. Mobilizing stakeholders around health product development areas, such as traditional medicines and diagnostics, would help to create trust between groups and build a stronger health innovation system.